Blood pressure control with active ultrafiltration measures and without antihypertensives is essential for survival in hemodiafiltration and hemodialysis programs for patients with CKD: a prospective observational study - Franklin Geovany Mora-Bravo; Pamela Tatiana Morales Torres; Nelson Rojas Campoverde; Guillermina Lucía Blum Carcelen; Juan Cristobal Santacruz Mancheno; Ángel Cristóbal Santacruz Tipanta; Hector Perez-Grovas; Willan Patricio Robles Abarca (BMC Nephrology)
Abstract Background High blood pressure is a prevalent condition in patients with chronic kidney disease on hemodialysis. Adequate control of high blood pressure is essential to reducing deaths in this group. The present study aimed to observe mortality prospectively in a group of patients in hemodialysis and hemodiafiltration programs in whom the use of antihypertensives was optimized with the point-of-care dry weight (POC-DW) technique. Methods The present observational, prospective study was carried out at the Pafram hemodiafiltration unit in Morona Santiago, Ecuador, and the hemodialysis unit of the Fundación Renal del Ecuador in Guayaquil, Ecuador, from August 2019 to December 2023. Patients who were receiving hemodiafiltration were included. Weight was optimized with POC-DW for eight weeks. In Group 1, patients whose use of antihypertensive drugs was not required to control systolic blood pressure with a value less than 150 mmHg predialysis, less than 130 mmHg postdialysis, and a peridialytic blood pressure (defined as post-HD minus pre-HD SBP) between 0 and − 20 mmHg were analyzed. In Group 2, patients who required antihypertensive drugs for not meeting the aims of systolic blood pressure were included. The variables included clinical, demographic, mortality, description of the treatment, and routine laboratory tests in dialysis programs. The sample was nonprobabilistic. Survival analysis was performed for the study groups. The log-rank test (Mantel-Cox) was used for survival comparisons. Results The study included 106 patients. Optimal blood pressure control without antihypertensive treatment was achieved in 52 patients (49.1%) (Group 1). In 54 patients (50.9%), antihypertensive agents were required (Group 2). There was more significant mortality in the group that received antihypertensives: 11 patients in group 1 (21.2%) versus 25 patients in group 2 (46.3%) (P = 0.005). Survival was more significant in group 1, with an HR of 2.2163 (1.125–4.158) (P = 0.0243). Conclusion In hemodiafiltration and hemodialysis programs, blood pressure control with active ultrafiltration measures and without using antihypertensives is essential for survival in patients with CKD.